Ulnar nerve entrapment at elbow in obstructive sleep apnea patients: a randomized controlled trial - ULUÇ, KAYIHAN (SPRINGER HEIDELBERG, 2017)
Obstructive sleep apnea (OSA) is a highly prevalent disease. For diagnostic and therapeutic purposes, OSA has been divided into several subgroups. Positional OSA (POSA), the most frequent subgroup (56 %), is described as overall apnea hypopnea index (AHI) 5 and supine AHI at least twice as high when compared to non-supine AHI. We aimed to investigate the frequency of ulnar nerve entrapment neuropathy at the elbow (UNEE) in OSA patients without clinical signs and symptoms of ulnar neuropathy and intended to find if sleeping position in OSA had an impact on UNEE development. Fifty POSA, 48 non-positional OSA (NPOSA) patients, and 45 healthy controls without diabetes mellitus, hypothyroidism, rheumatic diseases, and cervical radiculopathy underwent nerve conduction studies. We found that UNEE was highly frequent in OSA patients (42.9 %) and significantly more frequent in moderate to severe POSA patients than mild POSA patients (65.4 vs. 33.3 %, p < 0.05). Furthermore, when compared to non-positional ones, UNEE was significantly more frequent in moderate to severe POSA patients (65.4 vs. 36.4 %, p < 0.05). Our results showed that the severity of OSA in positional patients was correlated with increased frequency of UNEE. OSA patients should be informed about the predisposition of UNEE and questioned for the symptoms in periodical controls. POSA patients should be alerted about the additional effect of sleeping position on UNEE and the necessity of OSA treatment should be emphasized.
Keywords: Sleep apnea; Ulnar neuropathy; Positional sleep apnea; Ulnar nerve entrapment; Nerve conduction study; Sleeping position; TUNNEL-SYNDROME; CUBITAL TUNNEL; NEUROPATHY; PREVALENCE; SEVERITY; ADULTS; RISK; GUIDELINES; POSITION; HYPOXIA